1993
DOI: 10.1159/000187564
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Glycosaminoglycans in Different Phases of Balkan Endemic Nephropathy

Abstract: The relationship between glycosaminoglycans and β2-microglobulin, glycosaminoglycans and N-acetyl-β-D-glucosaminidase as well as the relationship between the chondroitin sulfate/heparan sulfate ratio and SDS electrophoresis in the urine of subjects from the endemic area of Balkan nephropathy was studied in order to establish a method for early detection of this disease. The results show an unquestionable increase in urinary excretion of total glycosaminoglycans in subjects with or suspected of havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In the last few years, we have had much experience with the routine use of SDS-PAGE in diagnosing nephrologic patients, and our recent results have shown that this method is suitable for the early diagnosis of BN and eventually for epidemiologic investigation in the endemic areas. Most probably because of the technical and financial advantages, SDS-PAGE will take the place of other methods proposed for the early diagnosis of BN (13,19,(31)(32)(33) although we do not know if this interdependence is valid for tubular damage of other origins. The same correlation should be examined for interstitial nephritis from other causes such as nephrotoxic, metabolic, immunosuppressive, and cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, we have had much experience with the routine use of SDS-PAGE in diagnosing nephrologic patients, and our recent results have shown that this method is suitable for the early diagnosis of BN and eventually for epidemiologic investigation in the endemic areas. Most probably because of the technical and financial advantages, SDS-PAGE will take the place of other methods proposed for the early diagnosis of BN (13,19,(31)(32)(33) although we do not know if this interdependence is valid for tubular damage of other origins. The same correlation should be examined for interstitial nephritis from other causes such as nephrotoxic, metabolic, immunosuppressive, and cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract tumors are often associated with BN (16,17). The protein concentration in the urine is lower than 1 g/L (18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation